USES OF COST DATA FOR PRODUCTION AN INVESTMENT POLICIES. - Doyle, Leonard A. (The Accounting Review, 1950)
The discussion of the accumulation and analysis of cost data for production and investment decisions raises a question about the basic procedure for accumulating the original cost data. Cost and production data are used for a variety of purposes: valuing inventories, determining profits or losses on individual orders or groups of products or operations, measuring efficiency of production, establishing prices, selecting the best of alternative methods of producing, measuring obsolescence and many other purposes. No single cost figure is equally satisfactory for all managerial decisions-some decisions require partial costs, others, such as the determination of obsolescence, require imputed cost such as interest. The central fact is that some of the decisions of management require a segregation of costs according to the extent to which they vary in total with the rate of output. A corollary of this is that none of the other decisions of management requires that cost and production data be accumulated on a basis inconsistent with the distinction between fixed and variable costs.